Paired Story Telling Cerita Bergambar Teknologi Pangan Kuliner Lokal Bali Meningkatkan Berbicara - Ketut Ayu Lola Monika; Ida Bagus Putrayasa Bagus Putrayasa; I Nyoman Sudiana; Sariyasa Sariyasa Sariyasa (JPG: Jurnal Pendidikan Guru, 2023)
Students lack the ability to properly express their opinions and use media, a class action research was conducted to improve students' speaking skills using the Paired Story Telling model supported by media images.The subjects of this review were 20 understudies from class III SDN 7 Sangsit Bali, and the data were investigated utilising subjective and quantitative distinct methods. The results of this study are pre-cycle students' speaking skills scores of 63.55 on average, 64 on the median, 62 on the mode, and 20% classical mastery; the students' speaking skills are not very good.The mean was 71.5, the median was 70, the mode was 63, and classical mastery was 65% in the first cycle.Speaking skills improved in cycle II, with mean 90, median 92, mode 92, and 90 percent classical completeness falling into the category of very good. As a result, the Paired Story Telling model supported by picture media improves elementary school students' speaking abilities